Characteristics of Contraceptive Acceptors to the Use of Contraceptive Types - Dhita Ayu Elvandri; Sri Winarsih; Mundarti Mundarti; Hilma Nadzifa; Arfiana Arfiana (Midwifery and Nursing Research, 2023)
Background: The success of family planning programs in Indonesia is influenced by several factors, including socio-economic, cultural, educational, religious, and women's status. At the South Magelang Health Center in 2022, it can be seen that in the first Quarter of 2022 there are 31 acceptors, both new and old acceptors with types of contraceptive method users injection 21, IUD 7, and Implant 2 acceptors Methods: the type of quantitative research with survey methods and data collection time with a cross-sectional approach. The research instrument used a questionnaire. The population is 31 respondents with data analysis using Chie Square with alpha 5%. Results: Based on statistical tests, the results obtained: there is no relationship between economic level p: 0.158, maternal age with p: 0.131, number of children with p: 0.887, education level with p: 0.778, level of knowledge about contraception with p: 0.642 and family support with p: 0.776 with the use of contraceptives. Conclusion: extensive and detailed information about various contraceptives is carried out before a person chooses to use certain types of contraception and husband support is needed in determining the type of contraception.